Prevalence and factors associated with anxiety among university students of health sciences in Brazil: findings and implications - Alves, Júlia Vasconcelos de Sá; Paula, Waléria de; Netto, Patrícia Ribeiro Rezende; Godman, Brian; Nascimento, Renata Cristina Rezende Macedo do; Coura-Vital, Wendel (Instituto de Psiquiatria da Universidade Federal do Rio de Janeiro, 2021)
ABSTRACT Objective The aim was to evaluate the prevalence and factors associated with anxiety disorders among university students of health sciences at Federal University of Ouro Preto, Brazil. Methods A cross-sectional study between March to June 2019. Data were collected through a self-administered questionnaire including sociodemographic, academic, family and behavioral issues. The Beck Anxiety Inventory was used to assess anxiety. Estimates were obtained through the prevalence ratio and Poisson multivariate analysis. Results Four hundred and ninety-three students participated with a mean age of 23.1 and predominantly women (79.9%). All students had some degree of anxiety, with the frequency of the severe, moderate and mild forms being 28.0%, 29.8% and 27.0%, respectively. The factors associated with anxiety included having suffered psychological and/or physical violence in childhood, having suicidal thoughts, having a deceased parent, living with parents, being dissatisfied with the course and being in the exam period. Conclusions The prevalence of anxiety was high in our study and family problems prior to entering university seem to significantly influence the degree of anxiety, which may compromise the student’s academic and social performance.